The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1440-1827.1986.tb01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Brain Lesion in Utero

Abstract: Two autopsy cases of cystic brain lesion in utero are reported. One of them was a donor infant of twin transfusion syndrome. The baby died immediately after birth and showed multicystic encephalomalacia in the distribution of the anterior cerebral artery. The second baby was a stillborn infant with thanatophoric dwarfism with associated chronic periventrlcular leukomalacia (PVL). It was suggested that the multicystic encephalomalacia and chronic PVL found in the first and second cases were caused by persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…The authors concluded that multicystic encephalomalacia and chronic PVL were caused by persistent circulatory disturbance in utero . 6 In the present patient, although mild fetal ventriculomegaly was noted from 22 weeks of gestation, PVE and cystic PVL were not observed during pregnancy. We speculate that some persistent circulatory disturbance, perhaps induced by a traumatic event, may have occurred before 22 weeks of gestation and fetal PVE may have developed at that time, but we were unable to obtain information about traumatic events that may have affected the mother.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The authors concluded that multicystic encephalomalacia and chronic PVL were caused by persistent circulatory disturbance in utero . 6 In the present patient, although mild fetal ventriculomegaly was noted from 22 weeks of gestation, PVE and cystic PVL were not observed during pregnancy. We speculate that some persistent circulatory disturbance, perhaps induced by a traumatic event, may have occurred before 22 weeks of gestation and fetal PVE may have developed at that time, but we were unable to obtain information about traumatic events that may have affected the mother.…”
Section: Discussioncontrasting
confidence: 46%
“…The second infant was stillborn at 30 weeks of gestation at a birthweight of 1030 g. An autopsy showed thanatophoric dysplasia with associated chronic PVL. The authors concluded that multicystic encephalomalacia and chronic PVL were caused by persistent circulatory disturbance in utero 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakamura et al . [ 52 ] have confirmed cystic brain lesions in two autopsy cases. One was a donor fetus in twin-to-twin transfusion syndrome, and the other was a case of thanatophoric dwarfism.…”
Section: Radiologic Findings Of White Matter Injury Of Prematuritymentioning
confidence: 83%
“…Chronic PVL was found in the second case. The findings observed in these cases imply that cerebral circulatory disturbance is a pathogenetic mechanism of in utero brain injuries [ 52 ].…”
Section: Radiologic Findings Of White Matter Injury Of Prematuritymentioning
confidence: 99%